RETRACTED: Digital volunteering of student youth: Awareness and willingness to participate - Eflova Maria; Maximova Olga; Garipova Regina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001